A NOVEL APPROACH TO THE MODEL APPRAISAL AND RESOLUTION ANALYSIS OF REGULARIZED GEOPHYSICAL INVERSION - Zhdanov M.S.; Tolstaya E. (My University, 2006)
The existing techniques for appraisal of geophysical inverse images are based on calculating the model resolution and the model covariance matrices. In some applications, however, it becomes desirable to evaluate the upper bounds of the variations in the solution of the inverse problem. It is possible to use the Cauchy inequality for the regularized least-squares inversion to quantify the ability of an experiment to discriminate between two similar models in the presence of noise in the data. We present a new method for resolution analysis based on evaluating the spatial distribution of the upper bounds of the model variations and introduce a new characteristic of geophysical inversion, resolution density, as an inverse of these upper bounds. We derive an efficient numerical technique to compute the resolution density based on the spectral Lanczos decomposition method (SLDM). The methodology was tested on 3D synthetic linear and nonlinear electromagnetic (EM) data inversions, and also to interpret the helicopter-borne EM data collected by INCO Exploration in the Voisey's Bay area of Canada. © 2006 Society of Exploration Geophysicists.
Keywords: GEOPHYSICAL SIGNAL PROCESSING; GEOPHYSICAL TECHNIQUES; INVERSE PROBLEMS